DEVELOPMENT OF SUSTAINABLE MOUNTAIN TOURISM IN PETROȘANI AREA, HUNEDOARA COUNTY - GABRIELA CORINA SLUSARIUC; CIPRIAN NIMARĂ (Annals of the University of Petrosani: Economics)
Mountain tourism specific to Petroșani Depression, includes a wide range of recreational, spiritual and economic activities taking place in various mountain areas. For Petroșani town, tourism could be an important economic source for the local community, generating jobs and income, ultimately, allow local organization and continuity of living in accordance with their own cultural traditions and origins. This paper aims to highlight the mountain tourism potential of this area and to give some alternatives for sustainable development.